Substance P enhances endogenous neurogenesis to improve functional recovery after spinal cord injury. (August 2017) - Yang, Lan; Li, Guilan; Ye, Jichao; Lu, Dihan; Chen, Zhihong; Xiang, Andy Peng; Jiang, Mei Hua
Abstract: Endogenous neural stem cells (NSCs) are the most promising sources for replacing cells lost after spinal cord injury (SCI). We have previously shown that substance P (SP), a neuropeptide, improves functional recovery after SCI and increases the numbers of cells in lesion sites, but how this occurs is unclear. Here, we investigate whether SP regulates the neurogenesis of resident NSCs as well as exerting a beneficial effect on functional improvement. We found that SP (5 nmol/kg) treatment markedly improved functional recovery and elicited robust activation of endogenous NSCs and boosted the number of EdU + proliferating cells differentiating into neurons, but it reduced astroglial differentiation in the lesion sites. Consistently, treatment with SP (10 nM) in vitro significantly increased the proliferation of NSCs via activating the Erk1/2 signaling pathway and promoted neuronal differentiation but not astroglial differentiation. These results suggest that SP may represent a potential therapeutic agent for SCI via enhancing endogenous neurogenesis.